PENGARUH PENDIDIKAN DAN PENGALAMAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. GLOBAL SARANA INFORMASI BERMUTU - Laurencia S. K; Setyo Riyanto (MIX: JURNAL ILMIAH MANAJEMEN, 2013)
Abstract: The purpose of this study is to determine the effect of education and workexperiences to employee performance at PT. Global Informasi Bermutu. Descriptivequantitative research methods by using statistical correlation an multiple regression withthe aim of analyzing the effect of the two independent variables (Education and WorkExperiences) on the dependent variable (Employee Performance). The sample used wasan employee of employees as much as 240 respondents who made a sample randomdetermination. The result research showed that from the analysis are known, alsodemonstrated from regression technique and significance, which states that both partiallyand jointly a positive and significant of employee performance. From two independentvariables, the education has the most dominant influence on employee performance.Keywords: education, work experiences, employee performance.